VIRUS: EVOLUSI, GENETIKA, DRIFT DAN SHIFT ANTIGEN - Yohanes Firmansyah; Edwin Destra; Juvenius Martin; Natasha Fiorentina Kusumawati; Michael, Michael; Nancy Suwarna (Pusat riset dan Inovasi Nasional, 2022)
Viral evolution is a subdiscipline of evolutionary biology and virology that focuses on the evolution of viruses. Many viruses, especially RNA viruses, have relatively high mutation rates and short production durations (on the order of one point mutation or more per genome per round of replication). The rapid pace of viral mutation paired with natural selection enables viruses to rapidly adapt to changes in the host environment, despite the fact that the majority of viral mutations offer little benefit and frequently prove to be harmful. Additionally, because viruses often make several copies in an infected host, altered genes can be rapidly transmitted to a large number of offspring. The high mutation rates of RNA viruses, which are the result of an error-prone RNA-dependent RNA polymerase, make them a veritable gold mine for researchers interested in discovering evolutionary novelty and developing new methods to study evolution in action. There are two different forms of genetic changes: antigenic drift and antigenic shift. This article covers briefly the evolution of viruses in terms of genetic variation.